Global Brain and the Future of Human Society. (June 2014) - Last, Cadell
The Global Brain is a leading hypothesis explaining the current evolution of the human system. Recent multidisciplinary research at the Global Brain Institute has laid a potential framework for thinking about the future of human society within the context of the emergence of a global brain this century. In this article, I outline the theory of challenge propagation and explain how this theory can help us formulate an empirical understanding of the future of individual and collective human experience with a global brain. This includes a prescriptive and predictive analysis of the future of governance and religion. The article invites discussion as well as critical and constructive feedback as its sole purpose is to stimulate a decentralized discussion that will help us all better understand the future of human organization in the twenty-first century.